A New Approaching Method for Linear Neutral Delay Differential Equations by Using Clique Polynomials - Yuzbasi, Suayip; Tamar, Mehmet Emin (Tubitak Scientific & Technological Research Council Turkey, 2023)
This article presents an efficient method for obtaining approximations for the solutions of linear neutral delay differential equations. This numerical matrix method, based on collocation points, begins by approximating y ' (u) using a truncated series expansion of Clique polynomials. This method is constructed using some basic matrix relations, integral operations, and collocation points. Through this method, the neutral delay problem is transformed into a system of linear algebraic equations. The solution of this algebraic system determines the coefficients of the approximate solution obtained by this method. The efficiency, accuracy, and error analysis of this method are demonstrated by applying it to several numerical problems. All calculations in this method have been performed using the computer program MATLAB R2021a.
Keywords: Neutral Delay Differential Equations; Collocation Method; Clique Polynomials; Approximate Solutions